Clinico-Pathological and Serological Characterization of Two Indian Field Isolates of Infectious Bursal Disease Virus - Gupta, A.; Sharma, P.C. (International Journal of Poultry Science, 2005)
The clinicopathological and serological characterization of two field isolates of infectious bursal disease virus (IBDV) recovered from vaccinated flocks that had been vaccinated against infectious bursal disease in Hoshiarpur (Punjab) and Hisar (Haryana) has been undertaken. Broiler chicks (26 days old) were inoculated with 105 p.f.u of Hoshiarpur isolate (group I) and 104 p.f.u. of Hisar isolate (group II) by oral plus intraocular routes. Although both field viruses produced lesions characteristic of IBDV, some differences in the nature and extent of damage were observed. Gross changes included: haemorrhages in the skeletal muscles, atrophy of bursa, haemorrhages in the intestine. The major histopathological lesions observed were: depletion of lymphocytes in both cortical and medullary regions of bursa, depletion of lymphocytes and reticular hyperplasia in spleen, coagulative necrosis in kidney, depletion of plasma cells in Harderians gland, and haemorrhagic foci in thymus. Both the isolates induced high levels of neutralizing antibodies in the sera of IBDV inoculated birds at 21 d.p.i. (log10 4.10 and log10 4.25 in group I and II respectively).